2017
DOI: 10.1039/c7cp03540c
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids for metal extraction from chalcopyrite: solid, liquid and gas phase studies

Abstract: We are pleased to submit for publication in Physical Chemistry Chemical Physics the attached manuscript entitled " Ionic liquids for metal extraction from chalcopyrite: solid, liquid and gas phase studies".In this work, we report an application of aqueous solutions of ionic liquids (ILs) based on imidazolium and ethylammonium cations, and hydrogensulfate, nitrate, acetate and dicyanamide anions in a complex study of leaching of Cu and Fe metals from naturally occurring chalcopyrite ore. This is the first study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The Arrhenius graph (Figure 8) was obtained with the apparent kinetic constants k d . The activation energy in the studied temperature range was 75.73 kJ/mol, similar to reported values for other IL systems [32]. The obtained results corroborate the proposed model for the system under study.…”
Section: Influence Of Temperature On Copper Extraction Ratessupporting
confidence: 88%
See 1 more Smart Citation
“…The Arrhenius graph (Figure 8) was obtained with the apparent kinetic constants k d . The activation energy in the studied temperature range was 75.73 kJ/mol, similar to reported values for other IL systems [32]. The obtained results corroborate the proposed model for the system under study.…”
Section: Influence Of Temperature On Copper Extraction Ratessupporting
confidence: 88%
“…The authors obtained the highest copper dissolution of 98.3% with 10% (v/v) of IL [hmim] [HSO 4 ] in an aqueous solution, with a particle size of under 45 µm, 25% hydrogen peroxide as an oxidant, a temperature of 45 • C, and a leaching time of 120 min. Kuzmina et al [32] studied chalcopyrite dissolution using the series 1-butylimidazolium hydrogen sulfate ([HC 4 ([bmim][OAc]), and found that the best IL to leach chalcopyrite was 1-butylimidazolium hydrogen sulfate, although the recovery rate was low without an oxidizing agent. Lastly, the ionic liquid [bmim][HSO 4 ] has shown the best performance in leaching mineral species, including refractory ores and precious metals [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Al-Zubeidei et al [36] studied the leaching of chalcopyrite with several structurally simple ionic liquids, and found that the progression of leaching was similar to that of H2SO4 solutions, and that more polar cations improve extraction. Kuzmina et al [37] studied chalcopyrite leaching in a series of ionic liquids in the absence of oxidants, and the 1butylimidazolium hydrogen sulfate composition showed the best performance. Still, the leaching ability of ionic liquids alone was insufficient to extract copper from chalcopyrite.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…31 Different authors have investigated the leaching of copper from the sulfidic copper ore chalcopyrite using ionic liquids. [32][33][34][35][36] The addition of polar organic solvents such as alcohols to the aqueous acidic solutions can increase the copper extractions. [37][38][39][40] Methanesulfonic acid, an organic acid was used as an alternative for mineral acid for extraction of copper from chalcopyrite.…”
Section: Introductionmentioning
confidence: 99%